Chinese pop culture’s development in the United States among Generation Z compared to South Korean pop culture - Lin, Zilun (Frontiers in Communication, 2025)
South Korean pop culture (K-pop) has achieved phenomenal business and cultural success in the United States, as evidenced by numerous hit songs, large-scale concerts, and record-breaking streaming and television viewership, particularly among Generation Z (Gen Z). In contrast, Chinese pop culture (C-pop) has experienced comparatively slower growth in the same market. While existing literature highlights the technological advancements and the business models of South Korean management companies as key drivers of K-pop’s success, there remains a research gap regarding the development and market performance of C-pop in the U.S. This qualitative study aimed to address that gap by conducting a comparative analysis of K-pop and C-pop in the U.S., specifically targeting Gen Z consumers. Utilizing a multiple case study methodology and a content analysis approach, this study examined the business models through numerical, textual, visual, and conceptual data derived from secondary sources. This study fills the gap in the existing literature by identifying the challenges facing C-pop in the U.S. market and proposing strategies for its growth. The findings suggest that a shift in creative direction, along with enhanced marketing strategies tailored to the U.S. market, is essential. Specifically, the study found that the American Gen Z audience prefers romance-themed and self-empowering content—whether in music or television—that establishes a personal connection and a sense of community. Therefore, it is strongly recommended that all aspects resonate with Gen Z population, a group of young individuals who experience loneliness.